Using the Technology of GIS in Estimating Equivalent Uniform Depth for Rainfall and Water Volume Resulted from this Rain Falling above Iraq for the Purposes of Planning and Development - AlGhazi, Hasan Sawadi Najeeban (Al-Adab Journal, 2020)
The present study aims at estimating the systematically equal Depth for the rainfall (millim) above Iraq and the water plate that is resulted from this rainfall which is (3 milers cubic meters) every year according to three scientific, geometrical and precise ways which are the Methods of Thiessen polygons, Isohyetal Method and the Method of arithmetic average. Those ways are used for gathering water and doing operations of development and typical planning for its management. It was dependent upon the depths of monthly rainfall recorded in forty three meteorological stations for the period (1980- 2013). There were some groups that were elicited from those rainfalls. Thirty one stations were located in Iraq and twelve of them were located out of Iraq (they were nearby to Iraqi borders). Those samples were used for guaranteeing the precision of drawing topographies and making statistical superficies in order to allocate the rain above Iraq. The researcher attempts to get that precision by using the best and modern technologies in applying which are represented in the technology of geographical information systems and their ability that is highly used in the structuring, treating the data basics and deriving samples spatial generating resulted from those samples. There are some results which are concluded in this research. One of them is the fact, that most of the ways are appropriate for estimating the equal and systematic depth for rainfall above Iraq, is the Isohyets Method and the two ways of Thiessen polygons and arithmetic average in this field are disable for estimating equal depth. In addition to what is mentioned above, the results refer that Iraq receive in the manual average a volume of rainfall which is 89, 073 milers cubic meters from water resulted from the equal and systematic depth which is 203, 76 milims.